Functionalization of reclaimed polyethylene with maleic anhydride and its application in improving the high temperature stability of asphalt mixtures. (15th June 2016) - Ma, Dechong; Zhao, Duijia; Zhao, Jingzhe; Du, Sujun; Pang, Jinyu; Wang, Wei; Fan, Changxin
Graphical abstract: Highlights: RPE-g-MAH was successfully prepared by a melt reactive process. DCP and MAH contents played the key role in DS and RD. High temperature performance of RPE-g-MAH modified asphalt mixture were investigated. RPE-g-MAH had superior rutting resistance towards the asphalt mixture. Abstract: A process to improve the properties of reclaimed polyethylene (RPE) polymer modified asphalt mixture by grafting of maleic anhydride (MAH) onto RPE (RPE-g-MAH) in the presence of dicumyl peroxide (DCP) as initiator was proposed. Fourier transform infrared spectra (FTIR) was employed to verify the grafting of MAH onto RPE. Modified asphalt mixture under different conditions were investigated on the RPE-g-MAH samples. To assess the effects of the RPE-g-MAH on the high-temperature stability of modified asphalt mixture, we discussed dynamic stability (DS) and rutting depth (RD) of modified asphalt mixture by studying the influences of various experimental parameters such as MAH content, DCP content, mixing temperature, wet mixing times and gradation type of mixture. Experimental results indicated that the RPE-g-MAH is feasible to improve high-temperature stability performance and low-temperature performance of asphalt mixture, and it could dramatically improve resistance to rutting of the asphalt mixture. Possible mechanism was proposed for RPE-g-MAH modification of asphalt mixture.